Netherland - O'Neill, Joseph (London : Harper Perennial, 2009)
Alone in New York, Dutchman Hans van den Broek seeks refuge in the game of his childhood - cricket. Years later a friend is found murdered and Hans is forced to remember his unlikely friendship with Chuck - a dreamer, visionary, and perhaps something darker 2009.
Originally published: London: Fourth Estate, 2008.
ENH
Karim International
Keywords: Male friendship -- Fiction; Cricket -- New York (State) -- New York; Separation (Psychology) -- Fiction; English literature